COVID-19 OUTBREAK AND CAPITAL MARKET REACTION: AN EVIDENCE FROM THE JAKARTA ISLAMIC INDEX 70 - Siti Amaroh (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
The COVID-19 outbreak has become a global problem affecting human life entirely. This paper provides evidence of the market reaction to Jokowi’s announcement regarding the first patient of COVID-19 in Indonesia on March 2, 2020. This research is an event study that looks at whether or not there is a difference in average abnormal returns of 'go public' companies registered on The Jakarta Islamic Index (JII) 70 both before and after the announcement. The observations were made 9 days before the announcement and 9 days after the announcement. Based on descriptive data, the average stock returns of JII 70 fluctuated which increased on the first day after the announcement but decreased sharply after the fifth day of the announcement. The test showed that the average abnormal returns are negative both before and after the announcement. The paired sample t-test provided evidence that there is a difference in the average abnormal return during the testing period between before and after the announcement. The market reacted negatively to the announcement indicated by negative average abnormal return and support a semi-strong market hypothesis.========================================================================================================Wabah Covid-19 dan Reaksi Pasar Modal: Bukti dari Jakarta Islamic Index 70. Wabah COVID-19 telah menjadi masalah global yang mempengaruhi kehidupan manusia sepenuhnya. Paper ini memberikan bukti reaksi pasar terhadap pengumuman Presiden Jokowi mengenai pasien perta COVID-19 di Indonesia pada 2 Maret 2020. Penelitian ini merupakan studi peristiwa yang melihat apakah terdapat perbedaan rata-rata abnormal return perusahaan go public yang terdaftar di Jakarta Islamic Index (JII) 70 baik sebelum maupun sesudah pengumuman. Pengamatan dilakukan 9 hari sebelum pengumuman dan 9 hari sesudah pengumuman. Berdasarkan data deskriptif, rata-rata return saham JII 70 mengalami fluktuasi yang meningkat pada hari pertama setelah pengumuman namun menurun tajam pada hari kelima setelah pengumuman. Hasil pengujian menunjukkan bahwa rata-rata abnormal return bernilai negatif baik sebelum maupun sesudah pengumuman. Uji-t sampel berpasangan memberikan bukti bahwa terdapat perbedaan rata-rata abnormal return selama periode pengujian antara sebelum dan sesudah pengumuman. Pasar bereaksi negatif terhadap pengumuman yang ditunjukkan oleh rata-rata abnormal return negatif dan mendukung hipotesis pasar semi-kuat.